Vegetative compatibility groups within Fusarium species isolates from tomato in Selangor, Malaysia - Ismaila, Abubakar Abubakar; Mohd Zainudin, Nur Ain Izzati (Universiti Putra Malaysia Press, 2018)
Vegetative compatibility provides valuable information on genetic diversity of certain fungal population including Fusarium species. Fusarium species are capable of causing mass spoilage of perishable vegetable fruits such as tomato either in the field or in storage. A total of 81 Fusarium isolates comprising F. oxysporum (54 isolates), F. semitectum (22 isolates) and F. subglutinans (5 isolates) were examined for vegetative compatibility groups (VCGs). Nit mutants were generated from minimal medium with chlorate (MMC) and potato dextrose agar with chlorate (PDC) media under varying degrees of chlorate (KClO3) concentrations from 4.5 - 6.0%. Four phenotyping media containing different nitrogen sources (NO2, NO3, NH4 and HX) were used to phenotype the Nit mutants into different classes: nit1, nit3 and NitM. All heterokaryon self-compatible (HSC) Nit mutants of Fusarium species were paired in all pairwise possible combinations on MM to classify them into VCG. Based on the index and distribution of the VCGs, isolates of F. oxysporum demonstrated high genetic diversity where 11 VCGs were recovered. Meanwhile, only three VCGs were recovered in F. semitectum isolates. Fusarium subglutinans isolates had the least number of VCGs where only two groups were recovered.